Do geopolitical risk, green finance, and the rule of law affect the sustainable environment in China? Findings from the BARDL approach. (March 2023) - Li, Zhuolun
Abstract: Keeping a sustainable environment in this era seems unrealistic due to numerous environmental factors; among those, carbon emission is the most daunting element to imbalanced the global sustainable environment. Such complications motivate the present authors to investigate the role of geopolitical risk, green finance, and the rule of law in attaining a sustainable environment in China. The data series of the years from 1995 to 2020 is tested through the Bootstrapped ARDL method under the theoretical framework of EKC theory. Before employing the BARDL technique, the descriptive analysis and unit root test is tested on the data to check the normality and validity of the data set. Afterward, the BARDL method for long- and short-run cointegration is analyzed based on the size and weak power characteristics. Finally, the Granger causality test proposed by Troster et al. (2018) is examined to check the cause and effect of geopolitical risk, green finance, and the rule of law with a sustainable environment. The Granger test identified the unidirectional causality among CE to GFIN and LAW, although other variables show the bi-directional causality. However, the results indicate the positive association of GPD and GPR with CE (carbon emission) in China's long-run and short-run data. A significant and negative relationship between the GFIN, GDP square, and the rule of law with CE is analyzed in both the long and short-run on the grounds of China's economy. In addition, the CUMSUM and CUMSUMsq test confirms the stability and reliability of the model. Furthermore, based on the findings, practical implications and limitations are developed to endure a sustainable environment in China. Highlights: Carbon emission is the most daunting element to imbalanced the global sustainable environment. The results indicate positive association of GPD and GPR with CE (carbon emission) in China's. A significant and negative relationship between the GFIN, and the rule of law with CE is observed. The results identified a unidirectional causality among carbon emission and LAW.